Bulgarian Biaspectual Verbs of the verba cogitandi and verba sentiendi Classes - Banasiak, Jakub Lubomir; Kiklewicz, Aleksander; Mazurkiewicz-Sułkowska, Julia (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article presents an analysis of the so-called biaspectual verbs of the verba cogitandi and verba sentiendi classes in the Bulgarian language. The study draws on Stanisław Karolak’s theory of semantic aspect. The analysis indicates that verbs traditionally considered biaspectual are by far more frequent in the category of mental verbs. A tendency towards biaspectuality is observed mainly in three-argument verbs. In terms of semantic approach to Slavic aspect, it can be concluded that the aspect of Bulgarian biaspectual verbs is expressed by a thematic morpheme rather than a suffix or prefix, as is typically the case in Slavic languages, and that its value is dependent on the temporal plane.